Analysis of The Effect of Mono Potassium Phosphate Fertilizer and Amino Acid Liquid Organic Fertilizer on The Quality of Melon Fruit (Cucumis melo L.) - Fadilla Eka Rohcahyani; Rahmanta Setiahadi (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Melon is a highly valuable horticultural commodity, and improving its fruit quality is essential for enhancingmarket competitiveness. The application of mono potassium phosphate fertilizer and liquid organic fertilizer (LOF)enriched with amino acids is expected to play a significant role in optimizing melon quality. This study aims toevaluate the effects of different dosages of mono potassium phosphate fertilizer and amino acid-enriched LOF onthe quality attributes of melon fruit. The research was conducted from April to July 2024 in a greenhouse locatedon agricultural land in Jatirejo Village, Nganjuk Regency. A total of 144 plants were used as research samples,arranged into 12 treatment combinations with three replications, with four plants per plot. The first treatmentfactor was the dosage of mono potassium phosphate fertilizer, with three levels: 5 g/plant, 10 g/plant, and 15g/plant. The second factor was the dosage of amino acid-enriched LOF, which included four levels: control, 50ml/plant, 100 ml/plant, and 150 ml/plant. Observed parameters included leaf number, fruit weight, fleshthickness, sweetness level, seed count, water content, and vitamin C content. The interaction between monopotassium phosphate fertilizer and amino acid-enriched LOF had a highly significant effect on fruit weight, fleshthickness, and seed count. Additionally, the interaction had a significant effect on leaf number and fruitsweetness. The combination of 15 g of mono potassium phosphate fertilizer and 100 ml of amino acid LOF perplant resulted in the highest fruit weight and optimal sweetness. This study highlights a novel integrativeapproach that combines inorganic phosphorus–potassium fertilization with amino acid–rich organic inputs toenhance melon fruit quality more effectively than single-factor applications. Based on these findings, it isrecommended that melon growers apply 15 g of mono potassium phosphate, combined with 100 ml of amino acidLOF, per plant to achieve superior fruit quality, particularly in terms of sweetness and overall yield.